Modern Tourism Management of Bangkok - Yuktananda, DR.Taschapat; Julkraianisong, Panjaree; Raicharoen, Dr. Sopangpak (Journal of Dhamma for Life, 2023)
The purposes of this research are as follows: 1) to study about modern tourism management of Bangkok 2) to analyze context of the problem in modern tourism management of Bangkok 3) to study and find the method to manage modern tourism management of Bangkok. This research used a quantitative research design. The sample group used were 400 people in the Lat Phrao area of Bangkok using a questionnaire to collect data. Then the data was analyzed using ready-made programs for social science research. The research found that Conditions of problems in modern tourism management in Bangkok. The primary variables in all aspects were found to be at a moderate level ( =3.05 S.D.=0.96), arranged in order from highest to lowest as follows. In terms of work methods, it is at a moderate level ( =3.21 S.D.=1.07). In terms of planning, it is at a moderate level ( =3.17 S.D.=1.01). In terms of operations, it is at a moderate level ( =3.04 S.D.=0.90). In terms of speed, it is at a level. Moderate ( =2.98 S.D.=0.93) and problem solving at the moderate level ( =2.86 S.D.=0.91), respectively. Guidelines for managing tourism in the modern era of Bangkok, the dependent variables, overall in all aspects, were found to be at a moderate level ( =3.15 S.D.=0.91), arranged in order from highest to lowest as follows. The needs aspect is at a moderate level ( =3.26 S.D.=0.96), the administration aspect is at a moderate level ( =3.14 S.D.=0.83), and the satisfaction aspect is at a moderate level ( =3.06 S.D.=0.94), respectively. The importance value of the factors influencing modern tourism management of Bangkok from all aspects significantly are operation method aspect X4 and problem-solving aspect X5. Both independent variables have coefficient of the predictor in raw score (b) equals 0.521 and 0.336 respectively.